Ectopic Expression of GsSRK in Medicago sativa Reveals Its Involvement in Plant Architecture and Salt Stress Responses - Sun, Mingzhe; Qian, Xue; Chen, Chao; Cheng, Shufei; Jia, Bowei; Zhu, Yanming; Sun, Xiaoli (Frontiers in Plant Science, 2018)
Receptor-like kinases (RLK) play fundamental roles in plant growth and stress responses. Compared with other RLKs, little information is provided concerning the S-locus LecRLK subfamily, which is characterized by an extracellular G-type lectin domain and an S-locus-glycop domain. Until now, the function of the G-type lectin domain is still unknown. In a previous research, we identified a Glycine soja S-locus LecRLK gene GsSRK, which conferred increased salt stress tolerance in transgenic Arabidopsis. In this study, to investigate the role of the G-type lectin domain and to breed transgenic alfalfa with superior salt stress tolerance, we transformed the full-length GsSRK (GsSRK-f) and a truncated version of GsSRK (GsSRK-t) deleting the G-type lectin domain into alfalfa. Our results showed that overexpression of GsSRK-t, but not GsSRK-f, resulted in changes of plant architecture, as evidenced by more branches but shorter shoots of GsSRK-t transgenic alfalfa, indicating a potential role of the extracellular G-type lectin domain in regulating plant architecture. Furthermore, we also found that transgenic alfalfa overexpressing either GsSRK-f or GsSRK-t showed increased salt stress tolerance, and GsSRK-t transgenic alfalfa displayed better growth (more branches and higher fresh weight) than GsSRK-f lines under salt stress. In addition, our results suggested that both GsSRK-f and GsSRK-t were involved in ion homestatis, ROS scavening, and osmotic regulation. Under salt stress, the Na+ content in the transgenic lines was significantly lower, while the K+ content was slightly higher than that in WT. Moreover, the transgenic lines displayed reduced ion leakage and MDA content, but increased SOD activity and proline content than WT. Notably, no obvious difference in these physiological indices was observed between GsSRK-f and GsSRK-t transgenic lines, implying that deletion of the GsSRK G-type lectin domain does not affect its physiological function in salt stress responses. In conclusion, results in this research reveal the dual role of GsSRK in regulating both plant architecture and salt stress responses.